The effects of a psychosocial support program on perceived stress of family caregivers of patients with mental disorders - Reihaneh Hajisadeghian; Sima Ghezelbash; Tayebeh Mehrabi (Wolters Kluwer Medknow Publications, 2021)
Background: Taking caring of patients with mental disorders is stressful and people who take care of these patients need to receive enough support and training to overcome this challenging situation. The present study was aimed at investigating the effects of a psychosocial support program on perceived stress of family caregivers of patients with mental disorders. Materials and Methods: This randomized controlled clinical trial was performed on 64 family caregivers of patients with mental disorders referred to Noor and Hazrat-e-Ali Asghar hospital in Isfahan, Iran, in 2018-19. The participants were randomly assigned to the intervention and control groups using a random number table. In the intervention group, the training program was held in 6 sessions of 90-minute training classes twice a week. Data were collected using a demographic characteristics form and the Perceived Stress Scale (PSS) before, immediately after, and 1 month after the intervention. Descriptive and inferential statistical tests such as Chi-square, Mann-Whitney, independent t-test, repeated measures ANOVA, and Kolmogorov-Smirnov test were used to analyze the data in SPSS software. Results: The result of the study showed that the total mean score of perceived stress in the intervention group was significantly less than the control group immediately after (F2=66.29, p<0.001) and 1 month after the intervention (F2=66.29, p<0.001). Conclusions: Delivering a training program on the different dimensions of support family caregivers need will reduce the perceived stress of family caregivers of patients with mental disorders. Therefore, the implementation of this intervention is recommended in this group of caregivers.